UMKM sebagai Wujud Nyata dalam Peningkatan Kesejahteraan Masyarakat - Zulfikar, Zulfikar; Dewi, Hartanti; Malahayatie, Malahayatie (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
Public awareness of fulfilling daily needs in this difficult era is increasing, it is hoped that people will not only be able to rely fully on the government, both the central government, provincial government and government at the district/city level but will be more active in processing existing resources. All the needs that we need in our daily lives should be able to be fulfilled optimally so as not to cause problems in the future. Micro, small and medium enterprises are the first step and of course can provide solutions to us personally and can also contribute to the community around us, rather than always relying on the government. There are many things we can actually do, as long as we want to, the choices are also clearly visible. This research is a qualitative research, direct questions are asked when used to collect data. The non-probability sampling method is used to select respondents from a population. The results of this study are Improving Community Welfare through UMKM. This research is expected to be input and a reference for the author personally and the author's environment, that fulfilling daily needs is mandatory, not only depending on the government but we must be able to survive in the face of reality in the midst of a difficult economy.